SURVIVAL OF PROSTATE CANCER PATIENTS WITH COMBINATION HORMONAL-RADIOTHERAPY BETTER THAN HORMONAL THERAPY - Hadibrata, Exsa; Tranggono, Untung (Indonesian Journal of Urology, 2020)
Objective: This study aims to determine the survival of prostate cancer (PCa) patients who did not undergo radical prostatectomy, but received hormonal therapy or a combination of radiotherapy and hormonal therapy. Material & Methods: This study was an observational analytic study with a retrospective cohort design, using secondary data to determine baseline data and diagnosis of patients, and using primary data to determine the survival of prostate cancer patients who received combination hormonal and radiotherapy therapy compared with hormonal therapy alone. The analysis was performed using chi-square and contingency coefficients to assess the relationship between survival with factors such as age, stage T, N, M, clinical stage, type of therapy, and prognosis. It also used the Kaplan Maeier curve to assess the survival picture of prostate cancer patients at Sardjito General Hospital. Results: 79 patients met the inclusion criteria. The mean age of the patients was 68 ± 8.4 years. A total of 52 (65.8%) patients received hormonal therapy, and 27 (34.2%) patients received combination hormonal and radiotherapy. There were 41 (51.9%) patients remain life, while 38 (48.1%) of patients died during the monitoring. We found that the Gleason score, PSA level, and clinical stage were significantly associated with patient survival with p <0.005. The 5 years survival rate patient with local, locally advanced clinical stage and PSA level ≤20 ng/ml who received combination hormonal and radiotherapy achieved 100%. Conclusion: Combination of hormonal and radiotherapy was more improving patient survival compared with hormonal therapy only in patient with locally advanced clinical stage, PSA level ≤20 ng/ml and Gleason score ≤7.